Pengaruh Citra Merek dan Kualitas Pelayanan terhadap Kepuasan Pasien di Klinik Mutiara I Kabupaten Bekasi - Marlina, Liza; Nurkamali, Ahmad (Ma'soem University, 2025)
Based on the results of observations and interviews, the background of this study is an insignificant increase in the last two years, which is thought to be caused by the lack of knowledge about brand image at the Mutiara I Clinic, Bekasi Regency. This study aims to determine how brand image affects patient satisfaction, determine how service quality affects patient satisfaction, and determine how brand image and service quality affect patient satisfaction simultaneously and partially at Mutiara I Clinic. The object of research in this report is to measure patient satisfaction at Mutiara I Clinic. The type of research is quantitative associative with primary data and uses data collection techniques in the form of observation, interviews, literature studies and questionnaires. While the sampling technique is non probability sampling with accidental sampling type. The population is patient visits at the Mutiara I Clinic which amounts to 15.074 patients per year using the Slovin formula totaling 100 respondents. The results showed that there was a significant influence between brand image on patient satisfaction, namely 38,4% with the results of the t test tcount> ttable value (7,811> 1,29025), there was a significant influence between service quality on patient satisfaction of 53.2% with the results of the t test tcount> ttable value (10,551> 1.29025). And simultaneously there is a significant.